1976
DOI: 10.1055/s-0028-1098406
|View full text |Cite
|
Sign up to set email alerts
|

The Endoscopic Demonstration of Coeliac Disease

Abstract: The first part of the duodenum has been studied endoscopically in treated and untreated coeliac patients. Biopsies taken from the duodenal cap during endoscopic examination, show villous atrophy similar to that found in the distal duodenum and jejunum. Using the indigocarmine scattering method, severe atrophy of the mucosal surface can be demonstrated throughout the duodenal cap, in vivo, in untreated coeliac disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 3 publications
2
19
0
1
Order By: Relevance
“…STEVENS and McCARTHY (18) reported that severe atrophy of the mucosal surface could be demonstrated throughout the duodenal cap using indigo carmine scattering with an Olympus GIF type D2 endoscope.…”
Section: Discussionmentioning
confidence: 99%
“…STEVENS and McCARTHY (18) reported that severe atrophy of the mucosal surface could be demonstrated throughout the duodenal cap using indigo carmine scattering with an Olympus GIF type D2 endoscope.…”
Section: Discussionmentioning
confidence: 99%
“…Before starting the study, the operators met to formally define, with the aid of endoscopic images, the endoscopic signs that were to be looked for in both adult [9,10,11,12] and pediatric patients [13,14]. These signs consisted of (1) mosaic pattern of the duodenal mucosa, (2) reduction or loss of the duodenal (Kerckring's) folds, (3) scalloping of the valvulae conniventes and (4) a nodular pattern of the bulbar mucosa (fig.…”
Section: Methodsmentioning
confidence: 99%
“…Reduced duodenal folds, scalloping of fold margins, mosaic pattern of mucosa and grooves in the mucosa are usual conventional endoscopic signs for celiac disease [50][51][52][53][54] . However these findings are not reliable in patchy [55,56] or milder cases of subtotal atrophy [57] .…”
Section: Celiac Diseasementioning
confidence: 99%